Neofunctionalization of zona pellucida proteins enhances freeze-prevention in the eggs of Antarctic notothenioids - Lixue Cao (Nature Portfolio, 2016)
Despite subzero temperature of their surroundings, eggs of Antarctic notothenioid fishes do not freeze. This study shows the expansion of genes related to freezing temperature in notothenioid which also acquired of ice melting-promoting zona pellucida proteins with specific structural properties.